Analisis Sistem Pengendalian Internal Berdasarkan Komponen Coso-Integrated Framework : Studi Kasus: Kantor Kelurahan Tanjung Mulia Hilir - Fidia Wati; Putri Kemala Dewi Lubis; Uswatul Akmalia; Mery Kristiani Susanti Simanjuntak (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyse the effectiveness of the implementation of the Government Internal Control System (SPIP) at the Tanjung Mulia Hilir Village Office. The method used is descriptive qualitative with the COSO (Committee of Sponsoring Organizations of the Treadway Commission) approach. Data was collected through interviews with the village secretary. The results showed that the Tanjung Mulia Hilir Urban Village Office has tried to implement ethical values and integrity, improve discipline through electronic attendance, and carry out main tasks and functions according to regulations. External supervision is carried out by the sub-district and neighbourhood security efforts through routine patrols. Internal communication makes use of instant messaging applications, while the community can submit complaints through the Head of Neighbourhood or the link provided. Community development and empowerment programmes are conducted through Musrenbangkel and the IPKK programme. Monitoring and evaluation is conducted through neighbourhood walkabouts. However, there is still a need to strengthen internal controls, optimise information technology, synergise empowerment programmes, and conduct more systematic monitoring and evaluation. With commitment and continuous improvement, it is expected that SPIP in Tanjung Mulia Hilir Village Office can realise effective, responsive, and public service-oriented governance.